Primary health care research in Saudi Arabia: A quantitative analysis - Jahan, Saulat; Al-Saigul, Abdullah Mohammed (International Journal of Health Sciences, 2017)
Objectives: The objective of this study was to analyze the published primary health care (PHC) research conducted in Saudi Arabia quantitatively and to determine the distribution of these research publications according to the topic, time, geographical location, and institution. Methods: In this descriptive study, we conducted literature search in PubMed and Google Scholar. The Medical Subject Headings terms: â€œPrimary Healthâ€ AND â€œSaudiâ€ and â€œPrimary Careâ€ AND â€œSaudiâ€ were used for searching relevant journal articles. Relevant information about the journal articles, published till December 2011, was recorded on a coding instrument. Results: From 1983 to 2011, a total of 655 PHC research articles were found. The publication output showed an increase with time. Original research articles (85.6%) were the main type of publications, and the most common study design was cross-sectional (93.4%). â€œChronic diseasesâ€ and â€œhealth services researchâ€ were the main topics addressed. Riyadh province had the highest proportion (46.3%) of publications, and the universities (56.2%), followed by the Saudi Ministry of Health (24.9%), were the main institutions publishing the research. Conclusion: Despite a well-established PHC setup in Saudi Arabia, the research outputs are low. Most of the published articles are cross-sectional studies and are conducted by the universities. Enhancing the PHC research by creating a supportive environment will lead to an increased evidence base for PHC and its effective translation into service delivery.